Research on circuit breaker failure protection and the secondary accelerated fault isolation scheme of VSC-HVDC grids - Li, Andi; Li, Botong; Wen, Weijie; Li, Bin; Chen, Xiaolong (Frontiers in Energy Research, 2023)
This paper proposes a direct current circuit breaker (DCCB) failure protection method and a secondary accelerated fault isolation scheme of voltage source converter based high voltage direct current (VSC-HVDC) grids. On the basis of considering the influence caused by the disconnection of opposite side DCCB, characteristics of fault current after the failure of DCCB are analyzed, and a circuit breaker failure protection method based on "increase current" discrimination is proposed. By analyzing the logical relationship among failed breaker re-tripping, adjacent DCCB action, the blocking of converter station and AC circuit breaker action, a secondary accelerated fault isolation scheme is proposed to minimize the fault isolation area. The proposed scheme achieves the accelerated isolation of DC faults after the failure of DCCB and avoids the trip of AC circuit breaker effectively by the re-tripping of the failed breaker.